The Effect of Digital Marketing on Increasing Sales Volume of Msmes In Makassar City - Mujahid, Mujahid; Syamsul Riyadi; Nasyirah Nurdin; Fitrah Aritama (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Marketing is any system or association that facilitates the market. Transactions that seek to satisfy human wants and desires are at the heart of marketing. Population used in This research is about micro, small and medium enterprises who use digital marketing in their marketing. The sample in this study was 73 respondents taken from several sub-districts in the city of Makassar. The data collection technique is by distributing questionnaires and documentation and validity and reliability testing has been carried out. And the data analysis techniques used are the heteroscedasticity test, simple linear regression analysis, and the T test with the help of SPSS Version 26 software. The results of the t test data analysis show a significant value for the influence of digital marketing (X) on sales volume (Y), where t calculated as 5.855 > t table value, namely 2.378. This matter shows that digital marketing variables has a positive influence on increasing the sales volume of MSMEs in Makassar City.